Pengaruh dewan pengawas syariah, ukuran perusahaan dan investment account holder terhadap pengungkapan Islamic social reporting dengan profitabilitas sebagai variabel moderating - Hariyanti, Anik; Annisa, Arna Asna (Journal of Accounting and Digital Finance, 2021)
The study examined the effect of DPS (sharia supervisory board), size, and investment account holder on Islamic social reporting with profitability as moderating variable (a case study of sharia commercial banks registered at OJK 2015-2020). The type of research is quantitative by using moderated regression analysis (MRA) as data analysis and using secondary data in the form panel. Based on the study results, it is shown that partially the DPS (sharia supervisory board), size, investment account holder have positive and significant on Islamic social reporting. Profitability can moderate the effect of size on Islamic social reporting but negatively moderate the DPS (sharia supervisory board) and investment account holder on Islamic social reporting.